Review Of Islamic Law On The Use Of Brong Exhaust And The Law In Selling It Review Of Islamic Law On The Use Of Brong Exhaust And The Law Of Buying And Selling It - Prof. Dr. M. Fahmi al-Amruzi, M.Hum; Raihan, Ahmad; M Yahya Adha Al Amien; Abdul Malik; Nasrullah; Nuril Khasyi`In (Sharia Journal and Education Center Publishing, 2023)
ABSTRACT This research discusses the use of brong exhaust and its trading practices in the context of Islamic law. The demand for motorcycle modifications has resulted in the increasing popularity of brong exhausts, which are often used for wild racing and produce annoying noise. In addition, many shops sell brong exhausts without considering the legal consequences. This research uses an empirical method with data collection through direct experience. The results of this study show that the use of a brong muffler is prohibited if it disturbs the comfort of others, even in religious situations such as reading the Qur'an. However, the use of brong exhaust is allowed if it does not disturb others, such as in official racing. In buying and selling practices, the seller is allowed if he does not know that the buyer will use it haram or if he sells it to an authorized racer. However, the seller may not sell the exhaust if he knows that the buyer will use it haram. Keywords: Islamic Law, Brong Exhaust, Sale and Purchase. ABSTRAK Penelitian ini membahas tentang penggunaan knalpot brong dan praktik jual belinya dalam konteks hukum Islam. Permintaan akan modifikasi sepeda motor mengakibatkan popularitas knalpot brong meningkat, yang sering digunakan untuk balap liar dan menghasilkan suara bising yang mengganggu. Selain itu, banyak toko yang menjual knalpot brong tanpa mempertimbangkan konsekuensi hukumnya. Penelitian ini menggunakan metode empiris dengan pengumpulan data melalui pengalaman langsung. Hasil penelitian ini menunjukkan bahwa penggunaan knalpot brong dilarang jika mengganggu kenyamanan orang lain, bahkan dalam situasi keagamaan seperti membaca Al-Qur'an. Namun, penggunaan knalpot brong diperbolehkan jika tidak mengganggu orang lain, seperti dalam balap resmi. Dalam praktik jual beli, penjual diizinkan jika tidak mengetahui bahwa pembeli akan menggunakannya secara haram atau jika menjualnya kepada pembalap resmi. Namun, penjual tidak boleh menjual knalpot jika mengetahui bahwa pembeli akan menggunakannya secara haram. Kata kunci: Hukum Islam, Knalpot brong, Jual beli.